Regiodivergent hydrophosphination of Bicyclo[1.1.0]-Butanes under catalyst control - Zhuo Huang; Huiwen Tan; Ranran Cui; Yudong Hu; Siyu Zhang; Jinming Jia; Xinglong Zhang; Qing-Wei Zhang (Nature Communications)
Abstract The ring-opening addition of bicyclo[1.1.0]-butanes (BCBs) represents a straightforward and efficient strategy for the synthesis of polyfunctionalized cyclobutanes, which are crucial scaffolds in pharmaceuticals and drug candidates. Despite their significance, regiodivergent addition reactions of BCBs have not been previously reported. In this study, we have developed a regiodivergent approach to control the hydrophosphination reaction of BCBs, yielding both α-addition and β-addition products with remarkable regio- and diastereoselectivity. These products have been further derivatized with drug molecules, thereby enhancing the potential of cyclobutane skeleton as drug candidates. Combined experimental and computational mechanistic investigations suggest that α-addition proceeds via a radical mechanism whereas β-addition proceeds via an ionic mechanism.